An Analysis of Students’ Difficulties in Reading Comprehension of Descriptive Text - Fauziah, Vira (SAFE-Network, 2024)
Many difficulties are experienced by students when understanding English text reading by Vocational High School (SMK) students. There are many factors that influence reading text. This study aims to help students in understanding English text so that the difficulties experienced by students in understanding descriptive text and the factors of difficulty that influence it can be known. This study was conducted on class I Culinary Arts students at State Vocational High School (SMKN) 9 Padang. The type of research conducted was descriptive qualitative research with data collection techniques used were questionnaires, interviews, observations and document analysis. The number of student subjects studied was 35 students. The results of this study were 69.5% of students experienced difficulties with very strong answers to the difficulties they found. As many as 23.1% of students experienced difficulties with the normal category. As many as 6.3% of students who did not experience difficulties were very difficult and as many as 1.1% of students did not experience difficulties at all. These results indicate that students with a strong category still find many difficulties in reading comprehension in the descriptive texts they have read. Meanwhile, the factors that influence the difficulty in understanding descriptive text reading are lack of vocabulary mastery, lack of motivation to learn English, learning without a tutor or learning online, and less supportive environmental or social factors. So, this study can help schools in taking action to further improve students' abilities that can help students in vocational schools.